Assessment of health-related quality of life in patients with inflammatory bowel disease in occupied Palestinian territory: a correlation cross-sectional study. (July 2021) - Smerat, Tasneem; Khdour, Maher; Abdoh, Qusay; Hallak, Hussein
Abstract: Background: Disease activity is suggested to be an important indicator for quality of life (QoL) in patients with inflammatory bowel disease (IBD). Few studies of the association between adherence to medication and QoL in patients with IBD are available, and their findings are conflicting. We examined associations between disease activity, medication adherence, and QoL in patients with IBD in occupied Palestinian territory. Methods: This correlation cross-sectional study was done from July 1, 2017, to Feb 30, 2018. We used convenience sampling to recruit patients from three major hospitals in southern and northern regions of occupied Palestinian territory. The disease-specific inflammatory bowel disease questionnaire (IBDQ) was used to examine QoL. Medication adherence was measured with the modified Morisky adherence scale. Associations were assessed by regression analysis. Results were analysed with SPSS version 20. The study was approved by the Al-Quds University Research Ethics Committee. Informed verbal consent was obtained from the participants before the start of the study. Interpretation: 132 patients were enrolled. The mean age was 34 years (SD 13) and 77 (58%) patients were men. Active disease in the previous 6 months was reported in 81 participants (61%). Low adherence to medication (score <6) was reported in 52 (39%) of participants. The average IBDQ score was low (150·72 [SD 30·08]), with the emotional and bowel domains being most affected. Active disease was the most significant factor associated with patients' QoL overall (p<0·001). No significant association was found between medication adherence and QoL. Regression analysis revealed significant independent associations between QoL and disease remission (p<0·001), high educational status (p=0·009), and using azathioprine (p=0·034). Interpretation: Our results provides baseline data about Palestinian IBD patients' QoL and medication use and adherence, and might help health-care providers to identify patients with IBD at risk of low QoL, especially those with relapse and active symptoms. Attention should be given by health-care providers and strategists to increasing knowledge about IBD. The importance of treatment adherence should be explored further. Some limitations were encountered during the study period; it was conducted in only three hospitals and the results might not be generalisable. The cross-sectional type of this study might prevent the identification of any cause-and-effect relationships, especially between medication and post-treatment improvements in QoL. Funding: None.